Analysis of Human Resources, Infrastructure, Budget, and Procedures on the Implementation Process of the PHBS Program in South Kalimantan - Nur Laily; Andini Octaviana Putri; Anggun Wulandari; Fauzie Rahman; Lia Anggraini; Nidaul Jannah; Lisa Salsa Billa; Siti Maimunah; Sri Wulandari; Nuralpisah Nuralpisah; Fitrya Hayati Alkamaliah (Journal of Health and Nutrition Research, 2026)
The Clean and Healthy Living Behavior Program (PHBS) is a strategic initiative of the Indonesian government aimed at improving the population’s health status through promotive and preventive approaches. In South Kalimantan, its implementation still faces tangible challenges, such as the high incidence of acute respiratory infections (ARI) and dengue hemorrhagic fever (DHF), as well as the low coverage of household PHBS practices. This study aims to evaluate the supporting and inhibiting factors affecting the implementation of PHBS in the region. The study employed a qualitative descriptive method with a purposive sampling technique. Eight informants were involved, consisting of officials from the Provincial Health Office, PHBS coordinators at the district/city level, health center staff from areas with the highest and lowest coverage, and community representatives. Data were collected through in-depth interviews, observation, and documentation, and then analyzed thematically. The results show that PHBS implementation is influenced by the interaction of supporting and inhibiting factors. Supporting factors include the availability of regulations, the commitment of health workers, and community participation. This condition results in the program’s implementation not yet being optimal, despite the existence of a policy framework. Therefore, improvements are needed in human resource capacity based on local needs, more stable funding mechanisms, and updated technical guidelines to ensure that PHBS implementation becomes more adaptive and effective in supporting community health development